MicroRNA-30 regulates left ventricular hypertrophy in chronic kidney disease - Jingfu Bao; Yinghui Lu; Qinying She; Weijuan Dou; Rong Tang; Xiaodong Xu; Mingchao Zhang; Ling Zhu; Qing Zhou; Hui Li; Guohua Zhou; Zhongzhou Yang; et al. (JCI Insight, 2021)
Left ventricular hypertrophy (LVH) is a primary feature of cardiovascular complications in patients with chronic kidney disease (CKD). miRNA-30 is an important posttranscriptional regulator of LVH, but it is unknown whether miRNA-30 participates in the process of CKD-induced LVH. In the present study, we found that CKD not only resulted in LVH but also suppressed miRNA-30 expression in the myocardium. Rescue of cardiomyocyte-specific miRNA-30 attenuated LVH in CKD rats without altering CKD progression. Importantly, in vivo and in vitro knockdown of miRNA-30 in cardiomyocytes led to cardiomyocyte hypertrophy by upregulating the calcineurin signaling directly. Furthermore, CKD-related detrimental factors, such as fibroblast growth factor-23, uremic toxin, angiotensin II, and transforming growth factor–β, suppressed cardiac miRNA-30 expression, while miRNA-30 supplementation blunted cardiomyocyte hypertrophy induced by such factors. These results uncover a potentially novel mechanism of CKD-induced LVH and provide a potential therapeutic target for CKD patients with LVH.